1977
DOI: 10.1007/bf01881014
|View full text |Cite
|
Sign up to set email alerts
|

Study of the7be(p, γ)-reaction

Abstract: The cross section of the 7Be(p, y)8B reaction has been determined at Ep = 360 keV to 0360 =0.17+0.04 lab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…Studies of high-energy neutrinos produced by 8 B decay in the sun have shown that when these neutrinos are detected on earth the number that remain electron neutrinos (ν e 's) is only about half of the number that have oscillated into other active species [1]. Precise predictions of the production rate of 8 B solar neutrinos are important for testing solar models, and for limiting the allowed neutrino mixing parameters including possible contributions of sterile species.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies of high-energy neutrinos produced by 8 B decay in the sun have shown that when these neutrinos are detected on earth the number that remain electron neutrinos (ν e 's) is only about half of the number that have oscillated into other active species [1]. Precise predictions of the production rate of 8 B solar neutrinos are important for testing solar models, and for limiting the allowed neutrino mixing parameters including possible contributions of sterile species.…”
Section: Introductionmentioning
confidence: 99%
“…ies of the 7 Be(p,γ) 8 B cross section [4,5,6,7,8,9,10,11,12,13,14,15], and indirect studies using Coulombbreakup [16,17,18,19,20] or peripheral heavy-ion transfer and breakup [21,22] reactions. The direct technique has the advantage that it studies the reaction that actually occurs in the sun, but is difficult experimentally because it requires a radioactive target or beam, and the cross sections are small.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations